Investment Experience, Financial Literacy, and Investment‐Related Judgments - Krische, Susan D. (Contemporary Accounting Research, 2019)
ABSTRACT This research examines how investment experience and financial literacy impact investment‐related judgments. Financial literacy refers to a person's knowledge of fundamental financial concepts. I begin by documenting investors' demographic characteristics and financial literacy using a relatively large sample of participants ( n > 2,000) recruited from Amazon's Mechanical Turk under different categories of investment experience, which I benchmark against national samples of financial capability skills in the United States. I then replicate a sample of three accounting research experiments, varying the type and depth of the underlying accounting issue. Across the three experiments, the data show two main results: First, investment experience strengthens the influence of financial accounting disclosures on participants' investment‐related judgments. Second, financial literacy further strengthens the influence of financial accounting disclosures on investors' (but not noninvestors') judgments. Collectively, these findings suggest that investment experience and financial literacy can help to identify individuals who are more likely to be able and willing to study financial reporting information with reasonable diligence as they form their investment‐related judgments.